Pelatihan dan Motivasi Siswa SMAN 1 Pangalengan dalam Meningkatkan Karir Akademik : Studi Lanjut Kepeguruan Tinggi - Aryana, Suhud; Nugraha, Via; Fauziya, Diena San; Setiawan, Teguh; Ermanto, Ermanto (IAIN Syekh Nurjati Cirebon, 2024)
TRAINING AND MOTIVATION OF SMAN 1 PANGALENGAN STUDENTS IN IMPROVING ACADEMIC CAREERS: ADVANCED HIGHER EDUCATION STUDIES. Training and academic motivation are crucial efforts to encourage high school students, particularly in remote areas such as Pangalengan, to pursue higher education. This study aims to raise awareness and motivation among students of SMAN 1 Pangalengan regarding the importance of continuing their studies to the university level. Through a participatory method with a qualitative descriptive approach, the program involved training and the dissemination of information about academic career pathways, including details on university entrance exams and scholarship opportunities. The results of the training indicated a significant improvement in the students' understanding and motivation. Before the training, 65% of students had limited knowledge about university admission pathways, but after the training, 85% of students reported an increased understanding. Additionally, the students' motivation to pursue higher education rose from 45% before the training to 78.6% afterward. These findings also demonstrate that the training successfully enhanced students' confidence in planning their academic careers. This program is expected to serve as an initial step in increasing student participation in higher education and assisting them in making appropriate academic career choices.